Multilingualism is a key for successful development of science and culture - Bukessovа, R. M.; Admanova, K. N. (ЗКАТУ им. Жангир хана, 2018)
Knowledge of native language and state language, learning foreign language widen students’ outlook, contribute polyhedral development, form tolerance and form view of the world. This definition gives us an idea of what should be a new generation. The experience of languages functioning in multinational countries proves bilingualism and multilingualism to be necessary and practically the only way of solving the problem of overcoming language barrier and ensuring easy communication of citizens of one and the same state formation speaking different languages.Около 70% населения во всем мире обладает знаниями двух и более языков, и это наиболее характерно для регионов на территории, населенной людьми разных национальностей. Знание родного языка и государственного языка, изучение иностранного языка расширяют перспективы студентов, способствуют многогранному развитию, формируют терпимость и вид мира
"Роль молодежи в развитии науки и инновации в ХХІ веке" в рамках программы "Рухани жаңғыру", посвящ. 20-летию столицы Республики Казахстан - города Астаны "Ел жүрегі - Астана" и 55-летию Западно-Казахстанского аграрно-технического университета имени Жангир хана: мат. третьей респ. науч.-практ. конф. студентов и магистрантов
Keywords: рк; конференции; отечественное издание; республиканская конференция; языкознание; государственный язык; полиязычие